Consumer Demand for Healthy Diet: New Evidence from the Healthy Eating Index - Zhifeng Gao; Xiaohua Yu; Jonq-Ying Lee (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
A large volume of literature has been focusing on the measure of diet quality and consumer demand for food. However, little has estimated consumer demand for diet quality. In this article, we systematically estimate consumer demand for diet quality using the healthy eating index (HEI) developed by the U.S. Department of Agriculture. The Results show that consumers have insufficient consumption of the food containing dark green, orange vegetable, legumes and total grain. Age and education have significant impact on consumer demand for diet quality but income does not. The own price elasticities of demand for diet quality are inelastic and are larger than cross price elasticities. Asymmetric cross price elasticity exists between the diet quality of solid fats, alcoholic beverages and added sugars and the quality of other diet groups. This information is critical in policies and programs that are designed to improve consumer healthy food choice which can reduce social cost of public health.
Keywords: D12; 330; Healthy Eating Index; Diet quality; Demand; Household production; Translog cost function